A Recruiting Maneuver Algorithm in Patients with Early Acute Respiratory Distress Syndrome - D. I. Levikov; D. A. Timashkov; A. Yu. Chervov; A. V. Biryukov; S. N. Dondokov (Общая реаниматология)
Objective: to evaluate the efficiency of a recruiting maneuver (RM) and adjustment of positive end-expiratory pressure (PEEP) in patients with early acute respiratory distress syndrome (ARDS). Subjects and methods. The study enrolled 16 patients (14 men and 2 women) aged 46 to 78 years (range 62±5.6 years) with ARDS of various genesis. RM was made, by stepwisely increasing PEEP and inspiratory pressure under the control of dynamic lung compliance and hemodynamic parameters. The values of blood gas composition and hemodynamics were determined during the study. Results. RM caused an increase in oxygenation index (OI) from 153.5±48.3 to 348.5±53.2 mm Hg. Oxygenation values returned to the baseline levels 30—40 min after the PEEP was set at the closure point of +2 cm H2O. If the set PEEP was 8—10 cm H2O higher than the objective, the effect of RM was retained for as long as 24 hours. When RM was performed using the maximum pressure of 50—60 cm H2O, the cardiac index (CI) was lower in all the patients and 30—50% of the baseline values were achieved in all cases, which required the optimization of cardiotonic therapy. The time of this pronounced reduction in cardiac output with RM was not longer than 5 min. After RM, during mechanical ventilation with 18—26 cm H2O PEEP, the CI did not practically differ from the baseline values (3.31±0.41 and 3.37±0.36 l/min/m2, respectively), though the dopamine dose required to maintain normal hemodynamics was somewhat higher (7.5±2.3 and 6.3±2.6 ^g/kg/min). Conclusion. Analysis of the given cases suggests that RM is highly effective in patients at the early stages of acute lung injury. The duration of RM effects may depend on the set PEEP level in individual cases. Setting PEEP at a level of +2—4 cm H2O fails to prevent repeated alveolar derecruitment in a number of patients. In these cases, it is expedient to individually adjust PEEP levels, by taking into account the long-term changes in OI and Cdyn. In this situation, PEEP may be set at a level of +8—10 cm H2O or at the maximum level that causes no hemodynamic disorders. Key words: acute respiratory distress syndrome, recruiting maneuver, alveolar derecruitment, positive end-expiratory pressure.